Regulation Of The Minister Of Trade No. 51/M-Dag/Per/7/2015 Concerning The Prohibition Of Importing Used Clothing: An Effort To Protect The Local Industry Or Hinder Consumer Choice? - Norhaifa Norhaifa; Nida Fitriani; Ayu Natasya; Anwar Hafidzi; Ahmad Muhajir (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This research examines Minister of Trade Regulation no. 51/M-DAG/PER/7/2015 concerning the Prohibition of Imports of Used Clothing in the context of protecting local industry and its impact on consumer choices in Indonesia. The research uses normative juridical methods with a literature study approach through analysis of various literary sources, statutory regulations and related scientific studies. The research results show that this regulation has a complex impact. On the one hand, this policy aims to protect the domestic textile industry and public health, supported by the findings of the Ministry of Trade which found dangerous microbial contents in imported used clothing. On the other hand, this ban has a significant impact on micro traders and lower middle class consumers who rely on used clothing as an affordable alternative. Challenges to policy implementation include difficulties in monitoring in the field and the continued prevalence of illegal import practices. The research recommends the need for a more balanced approach between protecting domestic industry and meeting.